Improving Early Childhood Tooth Brushing Habits: A Case Study at TK Kristen Anugerah Jakarta - Sisca, Sisca; Kurniawan, Yani; Hartanti, Monica Dwi; Orliando Roeslan, Muhamad (Lembaga Riset dan Inovasi Masyarakat Madani, 2025)
Maintaining oral hygiene from an early age is essential to prevent dental caries and gum diseases. However, many preschool children lack the knowledge and proper technique to brush their teeth effectively. This study aimed to evaluate the effectiveness of a structured tooth brushing training program at TK Kristen Anugerah Jakarta. Utilizing a participatory descriptive method, the program integrated interactive discussions, audiovisual demonstrations, and supervised practice sessions. A total of [jumlah peserta, jika tersedia] children participated in pre- and post-training assessments to measure improvements in their brushing habits. The findings showed significant gains: understanding the importance of brushing increased from 40% to 85%, brushing frequency improved from 20% to 65%, and correct brushing technique rose from 30% to 75%. These results suggest that school-based interactive training can positively influence children’s dental hygiene behavior. This study recommends incorporating such programs into early childhood education curricula and emphasizes the importance of parental involvement for sustaining long-term oral health practices.